Spices and Diplomacy of the Banten Sultanate with Foreign Kingdoms in the 16th- 19th Century - Syukron Jauhar Fuad Faizin (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
The Banten Sultanate was a pre-Indonesian Islamic kingdom from the 16th to early 19th centuries. Banten developed as a kingdom based on trade, its main commodity being pepper. In the 17th century, pepper became a spice with high value, so Banten used it as a diplomatic tool apart from being a trade commodity. As the destination of many foreign traders, it encouraged Banten to communicate with several kingdoms. Through historical research methods and a literature review, this article attempts to see diplomacy as one of the political activities of pre-Indonesian kingdoms. As a result, it can be seen that the Banten Sultanate carried out its diplomatic activities with several kingdoms, for example, Mecca (Ottoman), the Netherlands, England, Denmark, and France. This activity can be known from Banten's correspondence with the foreign kingdom and is supported by the chronicle narrative as colonial historiography. In this activity, the sultan of Banten often included several gifts, one of which was a large amount of pepper. Therefore, letters and other manuscripts can show Banten's position in diplomacy with other kingdoms, and pepper has an important role.